Implementation of School-Based Management in Increasing The Quality of Education - Jihan Jihan; Firman Ashadi; Iwan Sopwandin; Akhmad Ramli; Bashori Bashori (Departement of Mathematics Education, 2023)
The research aims to explain the implementation of School-Based Management (SBM) in an effort to improve the quality of education in one of the public high schools in South Tangerang City. The research approach used in this study is a qualitative approach with descriptive methods. This study aims to explain the implementation of SBM in improving the quality of education. The data obtained is presented in a descriptive form based on the results of interviews, observations and documentation studies. The research subjects in this study are information sources that can provide information or data related to the implementation of School Based Management (SBM) in an effort to improve the quality of education. In this study, the research subjects or informants were the Human Resources (HR) in schools including the Principal, Deputy Head of School for Curriculum, Head of Administration, Deputy Head of School for Facilities and Infrastructure, Deputy Head of School for Public Relations, and three teachers. School independence in meeting the availability of teaching and educational staff is sufficient, and school independence in meeting the availability of facilities and infrastructure is sufficient and sufficient. School partnerships/cooperation is good, this can be seen from the internal school relations that have been well established through work meetings, briefings and MGMP. Partnerships with external parties, the school has established partnerships with 13 institutions as evidenced by the MoU. Form of Participation, the form of participation is seen through the support of funds, facilities and staff from stakeholders in implementing school programs.